Effects of aeration on biodecolourisation of azo dye - Rakmi Abdul Rahman; Mohd. Ariffin Aton; Jailani Salihon (1990)
A study on the effects of aeration on biodecolourisation of an azo dye was carried out using acclimated culture. Oxidation reduction potential was used as a measure of degree of aeration. The results showed biodecolourisation to be dependent on degree of aeration with negative or very low oxidation reduction potential being favourable for decolourisation. This finding was in line with the postulation that biodecolourisation occurred via azo bond cleavage